Handbook of natural resource and energy economics. - Kneese, Allen V. (Allen Victor), 1930-; Sweeney, James L. (Handbooks in economics ;, 1985)
The three volumes comprising the Handbook of Natural Resource and Energy Economics examine the current theory, and sample current application methods for natural resource and energy economics. Volumes 1 & 2 deal with the economics of environmental and renewable resources, and are divided into six parts. The first deals with basic concepts, and subsequent sections are concerned with ethics and environmental topics. Volume 3 deals primarily with non-renewable resources. It analyzes the economics of energy and minerals and includes chapters on the economics of environmental policy.